2022
DOI: 10.1109/access.2022.3172319
|View full text |Cite
|
Sign up to set email alerts
|

Missing Value Imputation Designs and Methods of Nature-Inspired Metaheuristic Techniques: A Systematic Review

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 77 publications
3
9
0
Order By: Relevance
“…All these challenges have amplified the complexity associated with handling MVs. Nevertheless, finding studies that relate MLC and MV is not straightforward, as demonstrated in [4,8,17].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…All these challenges have amplified the complexity associated with handling MVs. Nevertheless, finding studies that relate MLC and MV is not straightforward, as demonstrated in [4,8,17].…”
Section: Plos Onementioning
confidence: 99%
“…These steps are repeated until the population is complete. Afterward, the mutation follows the established rate (lines [15][16][17][18][19][20]. The new population is arranged, and the iterative process continues until the stopping criterion is reached.…”
Section: The Evoimp Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to imputation, it is necessary to ensure that there is a sufficient amount of data for imputation. If a column has more than 50% of data missing, then it is dropped, and the attempt for imputation is dismissed. , Missingno and Bilogur’s method was used to illustrate the missing values. Missing values from the database are shown in Figure .…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%
“…However, this method has risks of losing important information in datasets, and it can significantly impact classification accuracy. Many other methods have been used and proposed in the literature to impute missing data for increasing classification accuracy [8], [9]. These methods can be classified into two principal categories; statistical-based methods, such as mean/mod and least squares (LS), and machinelearning-based methods like k-nearest neighbors (KNN), neural networks (NN), and decision tree (DT) [10].…”
Section: Introductionmentioning
confidence: 99%